PSYCHOEDUCATION REDUCES ANXIETY IN ELDERLY WITH HYPERTENSION IN NAMBAKOR VILLAGE SARONGGI DISTRICT SUMENEP - Emdat Suprayitno; Zakiyah Yasin; Istiqamatul Karamah; Dian Ika Puspitasari (Journal of Vocational Nursing)
Introduction: The problems in hypertension will cause emotional or mental disorders, one of which is anxiety. Feelings arise due to the fear and ignorance of an individual about hypertension experienced and the impact that will occur in the future. Psychoeducation is the provision of information about disease management and individual psychological aspects. This study aims to determine the effect of psychoeducation on the anxiety level of elderly patients with hypertension in Nambakor Village, Saronggi District.